Factors Associated with Pain Scores in Late Preterm and Term Infants Undergoing Routine Procedures - Rugsapol, Supranee; Amornjiraporn, Ittichote; Thanasanrpaiboon, Peerawit; Kitsommart, Ratchada (Siriraj Medical Journal, 2025)
Objective: To identify factors associated with Premature Infant Pain Profile-Revised (PIPP-R) scores in late preterm and term infants undergoing routine skin-puncture procedures. Materials and Methods: A secondary analysis of a prospective cohort study was conducted in hemodynamically stable late preterm and term infants (gestational age [GA] 34–41 weeks) undergoing routine procedures. PIPP-R scores were evaluated through video recordings by a blinded assessor. Results: Among 59 infants, 31 (52.5%) underwent venipuncture, 15 (25.4%) received intramuscular (IM) injections, and 13 (22%) underwent heelsticks. The median PIPP-R score was 11.0 [7.0, 14.0]. IM injections and heelsticks resulted in significantly higher pain scores compared to venipunctures (regression coefficient: 4.6, 95% CI: 2.3–6.8, and 2.8, 95% CI: 0.6–5.0, respectively). No correlation was observed between procedure duration and pain scores (r = -0.06, p = 0.68), but GA showed a weak positive correlation (r = 0.32, p = 0.01). After adjustment, low birthweight (<2500 g) was independently associated with lower PIPP-R scores (-2.9, 95% CI: -4.8, -1.1), while postnatal age <48 hours was linked to higher scores (5.8, 95% CI: 3.3–8.4). Oral sucrose solution significantly reduced pain scores (-6.4, 95% CI: -9.4, -3.3). Conclusion: IM injections were associated with the highest pain scores, while procedure duration did not affect pain intensity. LBW infants and those >48 hours old exhibited lower pain scores, suggesting developmental factors. The demonstrated efficacy of oral sucrose underscores its importance in neonatal pain management, emphasizing the need for routine implementation of analgesic strategies.